Analysis of Job Satisfaction, Work Stress and Compensation Against ASN Job Performance at Labuhanbatu South Sumatera North Department of Education - Rizal Ahmad (Yayasan Multidimensi Kreatif, 2023)
The study aims to find out how the influence of Work Satisfaction (X1), Work Stress (X2), and Compensation (X3) on the Work Performance (Y) of State Civil Appliances on the Department of Education of Labuhanbatu District of South Sumatra North with a sample amounting to 59 ASN. The study was conducted from March until May 2023. This study uses quantitative data processed with SPSS version 20.0 with a dual linear regression model. Data sources come from respondents collected through questionnaires. The results of the research showed that job satisfaction, work stress, and compensation have a positive and significant impact on the performance of the State Civil Appliances in the Labuhanbatu South District of North Sumatra Department of Education both partially and simultaneously. The compensation variable becomes the most dominant variable affecting the performance of the ASN 63.8% of the work performance can be described and obtained from the job satisfaction, work stress, and compensation, while the rest by other factors.